1989
DOI: 10.1152/ajpendo.1989.257.2.e180
|View full text |Cite
|
Sign up to set email alerts
|

In vivo insulin secretion and action in hyperglycemic rat

Abstract: This work was designed to study the effects of insulin secretion and action in vivo of moderate hyperglycemia induced by glucose infusion during 4 days in unrestrained rats. The maintenance of a glycemia around 170 mg/dl throughout the infusion time necessitated a gradual increase of glucose infusion rate from 11.5 to 19 g/day. Throughout the infusion period, plasma insulin-to-glucose ratio remained much higher in hyperglycemic rats (HG) than in controls. Glucose tolerance and insulin secretion tests were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
5
8
0
Order By: Relevance
“…Other laboratories have demonstrated similar adaptive physiology over the first 2-4 days of chronic glucose infusion in normal rats (20,40,41). Hager et al (15) showed diminished insulin sensitivity on day 3 relative to day 0, and although we could not directly compare insulin sensitivity during glucose infusion to day 0 before glucose infusion was begun, our data are consistent with these findings.…”
Section: Discussionsupporting
confidence: 87%
“…Other laboratories have demonstrated similar adaptive physiology over the first 2-4 days of chronic glucose infusion in normal rats (20,40,41). Hager et al (15) showed diminished insulin sensitivity on day 3 relative to day 0, and although we could not directly compare insulin sensitivity during glucose infusion to day 0 before glucose infusion was begun, our data are consistent with these findings.…”
Section: Discussionsupporting
confidence: 87%
“…Both mild and severe hyperglycemia in this spontaneously diabetic rat model appear to potentiate insulin secretion as reported previously in artificially hyperglycemic Wistar rats (28), rather than glucotoxicity and decreased p-cell function as reported by others (29,30). In the partial pancreatectomy dog model, glucose infusion caused impaired endogenous secretion after only 4 days, and islet loss also was shown (31).…”
Section: Discussionsupporting
confidence: 80%
“…Although insulin uptake is reportedly reduced during rat GI, yielding frank hyperglycemia (25), the rapid normalization of insulin levels in the present study could be the result of enhanced insulin clearance and/or increased insulin sensitivity under near-euglycemic conditions. The fact that another rat GI study clamping glucose levels at moderate hyperglycemia (170 mg/dl) observed increased tissue insulin sensitivity (24) suggests that this could be occurring in our model. We are currently addressing this possibility.…”
Section: Discussionmentioning
confidence: 84%